Shall we cooperate, or shall we compete? How network learning episodes influence strategic decisions in strategic networks. (16th May 2019) - Wegner, Douglas; Mozzato, Anelise Rebelato
The purpose of this paper is to examine how network learning influences decisions about cooperative or competitive strategies between strategic networks composed of small firms. This study responds to calls for research on network learning and focuses on developing an understanding of how network learning episodes shape the decisions of managers in strategic networks. We achieve this by analysing four Brazilian strategic networks, three of which decided to cooperate, while the fourth decided to continue competing. Data was collected through 18 interviews with network managers and network members to identify how network learning episodes happened in each strategic network. The results show that learning episodes were influenced by contextual factors and elements of content and processes, according to the network learning model of Knight and Pye (2005). We conclude by presenting theoretical and managerial implications for the field of collaborative strategies.